Cadmiun toxicology. Current concepts to determine environmental or occupational exposition by means of biological indicators - Ramírez, Augusto (2002)
With the beginning of the Industrial Era, specially after the II World War, man lives exposed progressively to more pollutants and has confronted huge environmental disasters like Minamata, Bophal, and Chernovyl. Cadmium is an environmental and industrial toxic pollutant that produces in man effects at the enzymatic, renal, respiratory and digestive levels, aggravated by its very extended mean life. To face this problem, we would have to make a survey of the principal sources of industrial pollution, mainly metallurgic, in order to protect the worker, applying TLVs and BEIs criteria concurrent with the state of the art.